Carbazole substituted amidinato silylene: synthesis, bonding, and coordination behavior with coinage metals - Ghosh, Moushakhi; Tothadi, Srinu; Khan, Shabana (Organometallics, 2021)
In this work, the synthesis and characterization of a new carbazole substituted amidinatosilylene (1) and its coinage metal complexes 3-8 are being reported. Before the complexation reactions, we prepared [PhC(N+Bu)(2)Si(Cbz)-> Co(CO)Cp] complex (2) to estimate the sigma-donating strength of the newly synthesized silylene 1. Further, several commonly available coinage metal salts were utilized for the complexation reactions with 1, which afforded complexes 3-8. The solid-state structures of 1-8 have been validated by single-crystal X-ray diffraction studies, NMR spectroscopy, and mass spectroscopy. DFT studies were also performed to understand the bonding scenario of 1 and 3-7. Of note, 1 consists of a HOMO on its carbazolide moiety, and the HOMO-1 features the silylene character. We also compared the HOMO-LUMO gap of 1 with other amidinato silylenes having different N-substitutions.